The COVID-19 pandemic impact on the best performers in athletics and swimming among Paralympic and non-disabled athletes - Schipman, J.; Sauliere, G.; Marc, A.; Hamri, I.; Le Topquin, B.; Rivallant, Y.; Difernand, A.; Toussant, J.-F.; Sedeaud, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The COVID 19 pandemic has greatly disrupted high performance sport and international competition. The aim of this study was to quantify the impact of the COVID-19 pandemic on the world`s top 10 performances in Athletics and Swimming among non-disabled and Paralympic athletes. METHODS: The results of the 10-best world performers in 66 Olympic events since 1891 and 255 Paralympic events since 2010 were collected. To quantify the performance trend, the slopes of the 4 years moving average were calculated and analyzed by time period. The distribution of performances (in % of the world record) by year was analyzed to compare the 2020 values to the ten previous years. The stability rate (athletes joining and leaving each year) since 2010 and the number of annual competitions events were also measured. RESULTS: Over the study period, such declines in performance have only been observed during the two World Wars. In 2020, the level of performances has decreased significantly, corresponding to a 6 to 10 years setback. In 2020, the number of new athletes in the 10-best was significantly higher with a lower number of organized competitions. CONCLUSIONS: The impact on the performances of the best international non-disabled and Para athletes has been considerable.